Bryophytes (Musci) unexpectedly rare or absent in the Azores. - Sjögren, Erik (2008)
Search for bryophytes in the Azores has until now resulted in a recording of about 430 species of mosses and hepatics. A few of these species are endemic to the Azores or to the Macaronesian island groups. The majority of the other species includes cosmopolitan or oceanic/suboceanic European species. This paper treats some mosses (Musci) which have not managed to get established in the Azorean bryovegetation. Some are just unexpectedly rare and frequently recorded as present in only one or two of the nine Azorean islands. All such species must overcome the gap between the Azorean islands and/or between the islands and the continents. This is quite possible, especially for richly diaspore-spreading species. However, I hypothesize that the principal hinder to the establishment of new bryophyte species, in the remote islands of the Azores, is the potent competition of already established bryo-communities on all sorts of substrates. Also, the influx of diaspores may not be large enough to secure an establishment there. The recent (last 50 yrs) influx of new species to the Azores has mainly been to sites within the low-altitude, profoundly maninfluenced landscape. There, competition from already established bryophyte species is much less potent than in the native plant communities in forest/shrub vegetation at altitudes above 500 m (cf. SJÖGREN 2003). Far-reaching changes of the composition of endemic Azorean bryo-communities within the remains of native Juniperus-Laurus-Erica forests are consequently not likely to take place within the near future. However, continued man-made changes within the Azorean high-altitude landscape, such as plantation of alien tree species, construction or improvement of roads and tracks, extension of areas of managed grasslands, plantation of invasive alien vascular plants may facilitate the influx of new bryophyte species, even there.